The Assessment of the Management and Attractiveness of Modern Playgrounds from the Points of View of Children and Designers - PODOLSKA Anna; RUSZKOWSKA Patrycja; ORZECHOWSKA-SZAJDA Iwona (Architecture, Civil Engineering, Environment)
A playground area dedicated to children is a place, whose attractiveness should encourage various forms of fun that manifests in physical, exploratory or cognitive activities. Based on the research conducted on one of the residential estates in Wroclaw, the authors attempted to evaluate the attractiveness of modern playgrounds for two groups of audiences: children, who are the direct users of these facilities, and designers of green areas. The playgrounds were assessed based on the functionality and aesthetics criteria. The preferences of both groups were analysed with the use of the SBE method, and the perception-based evaluation. The results revealed that for children, the most important factor is the functionality of the playground equipment, but they do not pay much attention to their appearance. As opposed to children, aesthetic attractiveness and functional appeal are equally important for designers. The obtained results allow us to better understand the needs of playground users, while, at the same time, they provide important guidelines for designers. Understanding the perception and the preferences of the youngest users in terms of the development of playground areas is essential for the education process of those, who design them.